Penerapan teknologi pemanenan air hujan menuju desa mandiri air bersih di Pulau Merbau - Joleha Joleha; Bambang Sujatmoko; Sri Djuniati; Haji Gussafri; Bochari Bochari; Andy Hendri; Suprasman Suprasman (Unri Conference Series: Community Engagement, 2019)
One of the efforts to overcome the clean water crisis in the archipelago, one of them is Merbau Island, is to make a simple technology that is used to accommodate excess water during the rainy season and next, the water can be utilized for various purposes when it has been needed. The technology is rainwater storage building (PAH). This community service activity was conducted by making a model of PAH building at one of the residents’ houses and conducting a counselling activity to residents in relation to both of calculation and planning of the PAH building, and also the importance of consuming clean water. The purposes of this community service are to give an understanding and increasing knowledge about the needed for rainwater harvesting technology so that daily clean water needs will be fulfilled by basic infrastructure of the ideal PAH system based on independent-communities. The volume of this rainwater reservoir is needed at 3 m3 (3,000 litres) from the roof area of 36 m2. This rainwater is used to meet the needs of drinking, cooking and washing of 15 litres/person/day. The number of residents in the house is 5 people. The results obtained from this activity are the construction of rainwater reservoirs with a volume of 1,000 litres with good and correct rainwater harvesting system equipment. Thus the lack of 2,000 litres of rainwater storage must be managed independently by the homeowner.